Nitric Oxide Crosstalk With Phytohormone Is Involved in Enhancing Photosynthesis of Tetrastigma hemsleyanum for Photovoltaic Adaptation - Xie, Zhuomi; Yang, Chuyun; Li, Mingjie; Zhang, Zhongyi; Wu, Yao; Gu, Li; Peng, Xin (Frontiers in Plant Science, 2022)
Photovoltaic agriculture is a newly emerging ecological planting pattern. In view of the adverse effect on production, a better understanding of photovoltaic adaptation responses is essential for the development of the innovative agriculture mode in sustainable crop production. Here, we investigated the impact of photovoltaic condition on endogenous hormone composition and transcriptome profile of Tetrastigma hemsleyanum. A total of 16 differentially accumulated phytohormones and 12,615 differentially expressed genes (DEGs) were identified. Photovoltaic adaptation significantly decreased the contents of phytohormones especially salicylic acid (SA) and jasmonic acid (JA). DEGs were the most relevant to photosynthesis and mitogen-activated protein kinase (MAPK) signaling pathway especially the key genes encoding proteins involved in photosystem I (PS I) and photosystem II (PS II) reaction center. Nitric oxide (NO), JA, and SA treatment alone significantly enhanced the photosynthetic efficiency which was decreased by exposure to photovoltaic condition, but the combined treatment of “NO + SA” could weaken the enhancement effect by regulating the expression level of psaL, CHIL, petF1, psbQ, and psaE genes. Exogenous phytohormones and NO treatment mitigated the accumulation of reactive oxygen species (ROS) and potentiated antioxidant capacity, which would be weakened by the combined treatment of “NO + SA.” SA and JA significantly decreased endogenous NO burst triggered by photovoltaic adaptation. SA might be a potent scavenger of NO and counter the restoration effect of NO on growth and photosynthetic potential in T. hemsleyanum. The results could provide reference for the application of phytohormones/other signaling molecules in photovoltaic agriculture.